COVID-19 Ramifications: A Scientific Approach to Bridge the Existing Gap between COVID Vaccines Hesitancy and Effectiveness - Nagy, Hassan; Hameed, Maha; Khan, Faryal; Co, Edzel Lorraine; Rauf, Unaiza (Avicenna Journal of Medicine, 2023)
The 2019 coronavirus disease (COVID-19) has been a major dilemma all over the world since December 2019. Several types of COVID-19 vaccines were developed for public utilization to halt the widespread of the disease; however, vaccine hesitancy is one major factor that prevents a successful control of this pandemic. This study aimed to summarize the different kinds of available COVID-19 vaccines and their effectiveness, and to assess the associated factors regarding vaccine hesitancy of the general population to bridge the gap existing between the two factors.13
Keywords: Covid-19; vaccine effectiveness; vaccine hesitancy; coronavirus